Pengaruh Model Problem Based Learning terhadap Kemampuan Menulis Karangan Deskripsi Subtema Indahnya Keberagaman Budaya Negeriku - Alin Nur Widia; Griet Hellena Laihad; Nur Hikmah (Medan Resource Center, 2022)
This study aims to determine of the ability to write descriptive essays of sub-theme the beauty of my country’s cultural diversity the application of problem-based learning models and conventional learning models. The calculation of the N-Gain of the problem-based learning model is 54,9 with moderate criteria, and the N-Gain value of the conventional model is 40,8 with moderate criteria. Researchers performed a normality test using the Liliefors test. Both samples are normally distributed because the value of both samples is less than Ltable. In the Problem Based Learning class, the value of Lcount is Ltable (0,048) (0,141), in the control class group, the value of Lcount is Ltable (0,077) (0,144). In the homogeneity test, the data is then homogeneous because Fcount Ftable is the value (1,04) ? (3,96). Furthermore, when testing hypotheses, the number of (6,63) was found to be larger than the table of (1,99547). Show that H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted. Based on the above research, it can be stated that of the ability to write descriptive essays of sub-theme the beauty of my country’s cultural diversity by the application of the Problem-Based Education Model.